2021
DOI: 10.3390/life11111143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Scopoletin from Penicillium janthinellum Snef1650 for the Control of Heterodera glycines in Soybean

Abstract: Soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is responsible for causing a major soybean disease globally. The fungal strain Penicillium janthinellum Snef1650 was evaluated against H. glycines. However, the effective determinants of the P. janthinellum strain are unknown. By performing pot experiments, a functioning compound was isolated from P. janthinellum Snef1650 through organic solvent extraction, semi-preparative HPLC, Sephadex LH-20 column chromatography, and silica gel column chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Scopoletin isolated from P. janthinellum Snef1650 was coated with soybean seeds and reduced the juveniles of H. glycines in the roots and cysts in the soil in the field assay. Meanwhile, scopoletin promoted the growth and yield of soybean plants [89]. Similarly, two P. oxalicum strains, NBC008 and NBC012, reduced the cyst number and improved the height and root length of soybean plants compared with the control [85].…”
Section: Biocontrol Microorganisms Strain Name and Reference Applicat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Scopoletin isolated from P. janthinellum Snef1650 was coated with soybean seeds and reduced the juveniles of H. glycines in the roots and cysts in the soil in the field assay. Meanwhile, scopoletin promoted the growth and yield of soybean plants [89]. Similarly, two P. oxalicum strains, NBC008 and NBC012, reduced the cyst number and improved the height and root length of soybean plants compared with the control [85].…”
Section: Biocontrol Microorganisms Strain Name and Reference Applicat...mentioning
confidence: 99%
“…Metabolite compounds from Streptomyces strains also exhibited remarkable effects against S. sclerotiorum [122]. Scopoletin was isolated from P. janthinellum Snef1650 and could decrease the number of cysts in the soil and juveniles in the soybean roots [89]. The L. enzymogenes C3 mutant was defective in antimicrobial secondary metabolite complex production and reduced the inhibitory effect on the reproduction of H. glycines [99].…”
Section: Biocontrol Mechanisms Of Controlling Soybean Diseasesmentioning
confidence: 99%
“…Yet, to our knowledge, there is no report on the correlation between nematode infection and the accumulation of coumarins in plants. However, recent studies revealed scopoletin to be a potent biocontrol agent against SCN, with scopoletin being active after the treatment of soybean seeds with the compound (Yan et al ., 2021). SCNs are in the same genus as H. schachtii and form a disease complex with F. virguliforme , thereby leading to stronger SDS severity of soybean (Westphal et al ., 2014; Xing and Westphal, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…19 In agricultural applications, Sco presents insecticidal activity, antibacterial sterilization action, nematicidal bioactivity, and allelopathy. 20,21 In our previous study, we found that Sco extracted from Artemisia annua exhibits strong acaricidal activity against CSM. 11 However, Sco is difficult to use commercially because it has poor water solubility and is strongly susceptible to photolysis.…”
Section: Introductionmentioning
confidence: 96%